Evaluation of the quality and effectiveness of some commercial microbial products in enhancing the growth and yield of soybean and maize - Asamoah, Gideon (2015)
A thesis submitted to the Department of Crop and Soil Sciences, Faculty of Agriculture, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the degree of Master of Science in Soil Science.